Kronik Hepatit B ve Hepatit C Olgularında Hepatit G Virüs Sıklığının Polimeraz Zincir Reaksiyonu (Pzr) ile Belirlenmesi - Özdarandeli, Aykut; Toraman, Zülal Aşçi; Doymaz, Mehmet Ziya; Bulut, Yasemin; Seyrek, Adnan; Kalkan, Ahmet (Fırat University, 2003)
Amaç: Bu çalışmada kronik HBV ve HCV hastalarında HGV sıklığının belirlenmesi amaçlanmıştır. Gereç ve yöntem: Çalışmaya 45 kronik hepatit B, 35 kronik hepatit C olgusu ve 50 sağlıklı kişi alındı. Serumlarda HGV RNA'sı 5' translasyona uğramayan bölgeye özgül primerlerle nested tersine transkripsiyon-polimeraz zincir reaksiyonuyla belirlendi. Bulgular: Kırkbeş kronik hepatit B'li hastanın 4'ünde (%8.9), 35 kronik hepatit C'li hastanın 7'sinde (%20) ve 50 sağlıklı kişinin birinde (%2) HGV RNA'sı bulunmuştur. Sonuç: Elde ettiğimiz bulgular istatistiksel olarak anlamlı bir fark olmamakla birlikte, HGV RNA sıklığının kronik hepatitis C hastalarında kronik hepatitis B hastalarına göre daha yüksek olduğunu göstermektedir.

Aim: The aim of this study was to investigate prevalence of Hepatitis G virus (HGV) was investigated among patients with chronic hepatitis B infection and chronic hepatitis C infection. Material and method: This study was performed on sera obtained from 45 patients with chronic hepatitis B infection, 35 patients with chronic hepatitis C infection, and 50 healthy controls. HGV infection was identified by a reverse transcription- nested PCR (RT-n-PCR) using primers derived from the 5' untranslated region (5' UTR). Results: The results indicated that HGV RNA was present in 4 of 45 (8.9%) patients with chronic hepatitis B infection, in 7 of 35 (20%) patients with chronic hepatitis C infection, and in one of 50 (2%) healthy controls. Conclusion: Although there was no significant differences, our results demonstrated that HGV RNA was detected more frequently in patients with chronic hepatitis C infection than in patients with chronic hepatitis B infection.
Detection of Hepatitis G Virus Infection By Polymerase Chain Reaction (Pcr) in Patients With Chronic Hepatitis B and Chronic Hepatitis C